PSVII-1 Effects of exogenous fibrolytic enzymes on the release of xylo-oligosaccharides from six varieties of wheat in-vitro. (5th December 2019) - Dale, Tom N; Parr, Tim; King, Julie; Brameld, John
Abstract: The study objective was to investigate the effects of in-vitro fibrolytic enzyme incubation on xylooligosaccharide (XOS) release from different wheat varieties. Six varieties of wheat were ground to a 300µm powder and subjected to total non-cellulosic hydrolysis with Trifluroacetic acid (TFA) and in-vitro incubations with one of three commercially available enzymes at their recommended doses: Econase XT (xylanase 160, 000 BXU/g), Econase MP1000 (Mannase 100, 000 MNU/g) or Econase BP700 (ß-glucanase 700, 000 BU/g) or no added enzymes. Each wheat variety was suspended (at 5mg/ml) in 50mM sodium citrate buffer (pH 5.2) with or without the individual enzymes (n = 3), and incubated at 40.7°C in a shaking incubator. Samples were taken at 0 and 6hr. Concentrations of xylose, xylobiose and xylotriose were determined by High-Performance Anion-Exchange Chromatography coupled with Pulsed Electrochemical Detection fitted with a CarboPac PA20 (xylose) or CarboPac PA200 Column (Dionex, Thermo Scientific) and known xylose and XOS standards (Megazyme, Ltd). Data were analysed by one or two-way ANOVA (Genstat 19th Edition), with significance accepted at P < 0.05. After TFA hydrolysis, there were significant differences between varieties (P < .001, ANOVA) in total xylose contents (Huntsman > Paragon > Chinese spring > Sinuelo > Highbury = Pavon 74). In the in-vitro incubations, there was a significant effect of enzyme, but not wheat variety, on both xylose (P = 0.009) and xylotriose (P < .001) release at 6 hours, with Econase XT releasing more than the other two enzymes. There was a significant enzyme x wheat variety interaction (P < .001) for xylobiose release at 6 hours, with Econase MP1000 releasing the most from Huntsman. In conclusion, the 6 wheat varieties differed in their non-cellulosic xylose contents and there were clear differences in the amounts of XOS released by the 3 enzymes. Further trials are needed to investigate whether the in-vitro experiments are indicative of results observed in-vivo.